The composition of Fusarium species in wheat husks and grains in south-eastern Poland - Adam Kuzdraliński; Michał Nowak; Hubert Szczerba; Karolina Dudziak; Marta Muszyńska; Justyna Leśniowska-Nowak (Journal of Integrative Agriculture, 2017)
Fusarium populations were investigated on 53 samples of wheat grains and husks collected approximately three weeks before harvest in 53 wheat fields in south-eastern Poland. A limited area of sample collection was chosen intentionally to avoid the effect of climate and weather variability. The study was conducted to assess the occurrence of 13 Fusarium species using species-specific PCR assays separately on grains and husks of winter wheat. The obtained data suggest that husks could take a protective role of wheat grain against Fusarium spp. The incidence of Fusarium species decreased in grains vs. husks from 29 to 100%. While Fusarium species were present in husks at 11.32% and less, they were absent in the grain. The presence of Fusarium species on husks is inversely proportional to the percentage reduction of Fusarium spp. in grain. There was a correlation of the presence of certain species of Fusarium in husks and in grains. The number of Fusarium species found on husks was about three times higher in comparison to wheat grain. In conclusion, the presented data indicate the importance of Fusarium populations analysis on wheat husk in seeds pathological studies.